Cerebrospinal Fluid Leak From the Orbital Roof During Orbital Exenteration. Issue 6 (November 2019) - Curragh, David S.; Valentine, Rowan; Selva, Dinesh
Abstract : Cerebrospinal fluid leaks are rarely encountered by orbital surgeons, but can occur during dacryocystorhinostomy, orbital decompression, orbital exenteration, and enucleation. The authors present a case of cerebrospinal fluid leak from an injury to the orbital roof during orbital exenteration with the use of monopolar cautery. This was repaired with multilayer closure. Surgeons performing orbital exenteration must be aware of the possibility of this complication when using monopolar electrocautery to transect the orbital contents at the apex during an exenteration. Injury to the orbital roof with monopolar cautery during orbital exenteration can result in cerebrospinal fluid leak, and orbital surgeons must be aware of the possibility of its occurrence.